2020
DOI: 10.1038/s41598-020-72013-7
|View full text |Cite
|
Sign up to set email alerts
|

Network science characteristics of brain-derived neuronal cultures deciphered from quantitative phase imaging data

Abstract: Understanding the mechanisms by which neurons create or suppress connections to enable communication in brain-derived neuronal cultures can inform how learning, cognition and creative behavior emerge. While prior studies have shown that neuronal cultures possess self-organizing criticality properties, we further demonstrate that in vitro brain-derived neuronal cultures exhibit a self-optimization phenomenon. More precisely, we analyze the multiscale neural growth data obtained from label-free quantitative micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
(69 reference statements)
1
23
0
Order By: Relevance
“…After understanding the related problems in the field of natural language processing, Shen et al [16] found that the research on word formation based on semantic perspective is of great significance to solve the ambiguity and polysemy of unregistered words and texts. Yin et al [17] combined conceptual integration theory with physical structure, which complements each other, and provided a good reference method for us to analyze the specific ways of semantic word formation. Chen et al [18] considered that noun use belongs to logical metonymy, which can be explained by event coercion in generative thesaurus theory, and put forward that physical structure is equivalent to noun and argument structure is equivalent to verb.…”
Section: Related Workmentioning
confidence: 99%
“…After understanding the related problems in the field of natural language processing, Shen et al [16] found that the research on word formation based on semantic perspective is of great significance to solve the ambiguity and polysemy of unregistered words and texts. Yin et al [17] combined conceptual integration theory with physical structure, which complements each other, and provided a good reference method for us to analyze the specific ways of semantic word formation. Chen et al [18] considered that noun use belongs to logical metonymy, which can be explained by event coercion in generative thesaurus theory, and put forward that physical structure is equivalent to noun and argument structure is equivalent to verb.…”
Section: Related Workmentioning
confidence: 99%
“…From genomic 1 , 2 , proteomic 3 , 4 , metabolic 5 , 6 , and physiologic 7 networks to microbial communities 8 , neural 9 , 10 , social 11 , 12 , material 13 , and technological 14 systems, we encounter complex interdependent networks with distinct dynamics yet unknown mechanisms of evolution and self-optimization. Although network science provides some metrics such as centrality and clustering coefficient that can shed light on localized connectivity patterns, we lack mathematical tools to quantify the degree of heterogeneity and complexity in the generating rules of a complex network that is the result of unknown evolving mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The structural and functional identifications of different neural types and related network topologies are important for the next-step research on biology-inspired artificial intelligence. Yin et al have analyzed degree centrality, closeness centrality, and betweenness centrality of conventional and clustered networks to better understand the biological efforts to optimize the network information transfer 36 . Hence, deeper integration of these multi-scale biologically-plausible inspirations with artificial or spiking neural networks is necessary towards brain-inspired artificial intelligence.…”
Section: Discussionmentioning
confidence: 99%